Trends in Chlamydia Screening Provision During Outpatient Visits for Young Women in the United States [26E]. (May 2017) - Flagler, Emily; Kobernik, Emily; Kamdar, Neil; Dalton, Vanessa
Abstract : INTRODUCTION: The purpose of this study was to 1) examine rates of chlamydia screening between 2005 and 2012, and 2) to identify visit characteristics associated with chlamydia screening during encounters with young women. METHODS: We used data from the 2005-2012 National Ambulatory Medical Care Survey, a nationally representative sample of physician-reported, office-based medical visits. Bivariate analysis was performed to compare office visit characteristics among women 14-20 yo and 21-25 yo, respectively, and by time period of screening (period 1: 2005-2008, period 2: 2009-2012). Multivariable logistic regression with appropriate survey weights was performed for all office visits to identify predictors of chlamydia screening and subsequent age-stratified models were developed to identify independent predictors of chlamydia screening. RESULTS: Among 16, 707 office visits, the overall chlamydia screening rate was 2.7% and 4.2% among 14-20 yo and 21-25 yo, respectively. Age, race, provider type, and visit type were associated with screening during an office visit. After risk adjustment, the odds of receiving chlamydia screening were significantly higher during period 2 (aOR=1.28, 95%CI: 1.01-1.63), among women aged 21-25 (aOR=1.56, 95%CI: 1.22-1.99), among non-Hispanic blacks (aOR=2.12, 95%CI: 1.60-2.81), and during preventive care visits (preventive care: aOR=12.95, 95%CI: 7.93-21.2). In age stratified models, preventive care visits, and being seen by an obstetrician-gynecologist were significant predictors of screening in both age groups, however non-Hispanic black race was a predictor only for visits among 21-25 yo. CONCLUSION: Chlamydia screening rates during outpatient visits remain low despite clinical guidelines. Visit characteristics are associated with screening and suggest intervention strategies to improve screening rates.